2019
DOI: 10.1128/aem.02749-18
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Supplementation of In Vitro Fecal Fermentations Inhibits Proteolysis by Gut Bacteria, and Host Diet Shapes Gut Bacterial Metabolism and Response to Intervention

Abstract: Metabolism of protein by gut bacteria is potentially detrimental due to the production of toxic metabolites, such as ammonia, amines, p-cresol, and indole. The consumption of prebiotic carbohydrates results in specific changes in the composition and/or activity of the microbiota that may confer benefits to host well-being and health. Here, we have studied the impact of prebiotics on proteolysis within the gut in vitro. Anaerobic stirred batch cultures were inoculated with feces from omnivores (n = 3) and veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 66 publications
2
27
0
1
Order By: Relevance
“…Some studies also showed that prebiotics, such as fructooligosaccharide and xylooligosaccharide, had an inhibitory effect on proteolysis (Lecerf et al, 2012). These results therefore suggested that inulin might decreasing the availability of amino acids for proteolytic bacteria, thus reducing ammonia production (Wang et al, 2019). Microbial metabolites derived from the fermentation of amino acids or proteins, mainly ammonia, amines, indole compounds, and hydrogen sulfide, are potentially detrimental to gut integrity, which could be responsible for SE-infectionrelated impairment of the mucosal barrier (Song et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Some studies also showed that prebiotics, such as fructooligosaccharide and xylooligosaccharide, had an inhibitory effect on proteolysis (Lecerf et al, 2012). These results therefore suggested that inulin might decreasing the availability of amino acids for proteolytic bacteria, thus reducing ammonia production (Wang et al, 2019). Microbial metabolites derived from the fermentation of amino acids or proteins, mainly ammonia, amines, indole compounds, and hydrogen sulfide, are potentially detrimental to gut integrity, which could be responsible for SE-infectionrelated impairment of the mucosal barrier (Song et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…The result was a substantial progression of gastrointestinal and neuro-behavioral [ 52 ]. Cumulative research findings pointed to a range of metabolites produced by Clostridiaceae , which include indole derivate phenols and p-cresol [ 53 , 54 , 55 ]. The toxin-producing Clostridia are glyphosate-resistant bacteria, and the exposure of children to this environmental pesticide may increase the abundance of Clostridia in their guts, which can lead to ASD progression [ 56 ].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…On the contrary, proteolytic fermentation occurs in the distal colon, producing branched-chain fatty acids (BCFAs) and potentially detrimental metabolites such as ammonia (from amino acid deamination and urea hydrolysis), indoles, and phenols (from amino acid (AAs) carboxylation). Therefore, the intake of foods composed entirely of animal or plant ingredients alters the microbial community [29,31].…”
Section: The Dietary Impact On Gut Microbiota and Metabolic Compositionmentioning
confidence: 99%